Increasing nitrogen supply to phosphorus-deficient Medicago sativa decreases shoot growth and enhances root exudation of tartrate to discharge surplus carbon dependent on nitrogen form - Honghua He; Zekun Zhang; Qi Peng; Chao Chang; Rui Su; Xiao Cheng; Yingxin Li; Jiayin Pang; Sheng Du; Hans Lambers (Plant and Soil, 2021)

Carbonaceous nanoparticles in Zibo hot springs: Implications for the cycling of carbon and associated elements - Xiaobo Tan; Benyu Bo; Peng Zhang; Guangyu Shao; Rui Liu; Kun Wang (Environmental Chemistry Letters, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Microbial ecology of sulfur cycling near the sulfate–methane transition of deep‐sea cold seep sediments - Wen‐Li Li; Xiyang Dong; Rui Lu; Ying‐Li Zhou; Peng‐Fei Zheng; Dong Feng; Yong Wang (Environmental Microbiology, 2021)
Summary Microbial sulfate reduction is largely associated with anaerobic methane oxidation and alkane degradation in sulfate–methane transition zone (SMTZ) of deep‐sea cold seeps. How the sulfur cycling is mediated by microbes near SMTZ has not been fully understood. In this study, we detected a shallow SMTZ in three of eight sediment cores sampled from two cold seep areas in the South China Sea. One hundred ten genomes representing sulfur‐oxidizing bacteria (SOB) and sulfur‐reducing bacteria (SRB) strains were identified from three SMTZ‐bearing cores. In the layers above SMTZ, SOB were mostly constituted by Campylobacterota, Gammaproteobacteria and Alphaproteobacteria that probably depended on nitrogen oxides and/or oxygen for oxidation of sulfide and thiosulfate in near‐surface sediment layers. In the layers below the SMTZ, the deltaproteobacterial SRB genomes and metatranscriptomes revealed CO 2 fixation by Wood–Ljungdahl pathway, sulfate reduction and nitrogen fixation for syntrophic or fermentative lifestyle. A total of 68% of the metagenome assembled genomes were not adjacent to known species in a phylogenomic tree, indicating a high diversity of bacteria involved in sulfur cycling. With the large number of genomes for SOB and SRB, our study uncovers the microbial populations that potentially mediate sulfur metabolism and associated carbon and nitrogen cycles, which sheds light on complex biogeochemical processes in deep‐sea environments.

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Analytical solution of grouting fracturing height for the post-grouted bored piles using the Herschel–Bulkley model with time-varying viscosity - Gan Nan; Hai-ming Liu; Yong-mei Peng; Rui Liang; Hong-tao Xie; Jing Cao (Arabian Journal of Geosciences, 2021)

Insights into heat response mechanisms in Clematis species: physiological analysis, expression profiles and function verification - Hao Zhang; Changhua Jiang; Rui Wang; Long Zhang; Ruonan Gai; Siyuan Peng; Yi Zhang; Chanjuan Mao; Yuxia Lou; Jianbin Mo; Shucheng Feng; Feng Ming (Plant Molecular Biology, 2021)

Construction and application of easy-to-detect cyanobacteria with vp28 gene - Min-Min Zhuang; Wen Peng; Yang Xu; Xiao-Hui Jia; Ding-Ji Shi; Pei-Min He; Rui Jia (Journal of Applied Phycology, 2021)

Temperature and Moisture Modulate the Contribution of Soil Fauna to Litter Decomposition via Different Pathways - Bo Tan; Rui Yin; Jian Zhang; Zhenfeng Xu; Yang Liu; Shuqin He; Li Zhang; Han Li; Lixia Wang; Sining Liu; Chengming You; Changhui Peng (Ecosystems, 2021)

The long-term trend of Bohai Sea ice in different emission scenarios - Donglin Guo; Rui Li; Peng Zhao (Acta Oceanologica Sinica, 2021)

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Water Qualities and Products Generated in Dechlorination Process Using Ultra-high Lime with Aluminum Method - Jiali Xu; Peng Chen; Chen Dou; Di Yin; GuangYuan Meng; Rui Cheng; Haifeng Liu; Lehua Zhang (Water, Air, & Soil Pollution, 2021)

The resurgent landscape of xenotransplantation of pig organs in nonhuman primates - Xuan Zhang; Quancheng Wang; Jingjun Zhao; Xiao Li; Wei Peng; Zhaoxu Yang; Zhibin Lin; Long Yang; Rui Ding; Kaishan Tao; Kefeng Dou (Science China Life Sciences, 2021)

Different physiological responses of C3 and C4 plants to nanomaterials - Tonghao Bai; Peng Zhang; Zhiling Guo; Andrew J. Chetwynd; Mei Zhang; Muhammad Adeel; Mingshu Li; Kerui Guo; Ruize Gao; Jianwei Li; Yi Hao; Yukui Rui (Environmental Science and Pollution Research, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Correction to: Strong phosphorus (P)-zinc (Zn) interactions in a calcareous soil-alfalfa system suggest that rational P fertilization should be considered for Zn biofortification on Zn-deficient soils and phytoremediation of Zn-contaminated soils - Honghua He; Miaomiao Wu; Rui Su; Zekun Zhang; Chao Chang; Qi Peng; Zhigang Dong; Jiayin Pang; Hans Lambers (Plant and Soil, 2021)

Effects of oxytetracycline on plant growth, phosphorus uptake, and carboxylates in the rhizosheath of alfalfa - Zekun Zhang; Rui Su; Chao Chang; Xiao Cheng; Qi Peng; Hans Lambers; Honghua He (Plant and Soil, 2021)

Strong phosphorus (P)-zinc (Zn) interactions in a calcareous soil-alfalfa system suggest that rational P fertilization should be considered for Zn biofortification on Zn-deficient soils and phytoremediation of Zn-contaminated soils - Honghua He; Miaomiao Wu; Rui Su; Zekun Zhang; Chao Chang; Qi Peng; Zhigang Dong; Jiayin Pang; Hans Lambers (Plant and Soil, 2021)

Copper-induced sublethal effects in Bufo gargarizans tadpoles: growth, intestinal histology and microbial alternations - Rui Zheng; Minyao Wu; Hongyuan Wang; Lihong Chai; Jufang Peng (Ecotoxicology, 2021)

Space–time variations of sea ice in Bohai Sea in the winter of 2009–2010 simulated with a coupled ocean and ice model - Rui Li; Youyu Lu; Xianmin Hu; Donglin Guo; Peng Zhao; Ning Wang; Kenneth Lee; Baiyu Zhang (Journal of Oceanography, 2021)

Numerical simulation study of influencing factors for 3D coal seam gas drainage efficiency - Yuexia Chen; Tingxiang Chu; Xuexi Chen; Peng Chen; Junhong Si; Rui Peng (Arabian Journal of Geosciences, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Safety Analysis Control Measures of Multiple Mining Soft Rock Roadways - Rui Peng; Meiling Fang; Ruile Ren; Qifeng Zhao; Hanwen Jia (Geotechnical and Geological Engineering, 2021)

Change detection in SAR images based on superpixel segmentation and image regression - Rui Zhao; Guo-Hua Peng; Wei-dong Yan; Lu-Lu Pan; Li-Ya Wang (Earth Science Informatics, 2021)

How can the winter North Atlantic Oscillation influence the early summer precipitation in Northeast Asia: effect of the Arctic sea ice - Peng Zhang; Zhiwei Wu; Rui Jin (Climate Dynamics, 2021)

Study on Support Technology of Deep Mine Roadway in Xingdong Coal Mine - Jianjun Shi; Jicheng Feng; Rui Peng (Geotechnical and Geological Engineering, 2021)